Analysis of Patient Preferences in Choosing Health Services at Ibnu Sina Islamic Hospital Pekanbaru - Rina Sabri; Fahmi Oemar; Helwen Heri (SAINS ORGANISASI, 2022)
To survive and develop sustainably, hospitals must be able to respond to the dynamics of change by knowing patient preferences to be able to provide quality health services. This study was conducted on inpatients at RSI Ibnu Sina Pekanbaru with the aim of knowing the factors that influence patient preferences from location, socio-economic factors, service quality and patient satisfaction as an intervening. The research population was conducted on inpatients at RSI Ibnu Sina Pekanbaru with a research sample of 150 people who were taken by simple random sampling method. The study used quantitative analysis and descriptive statistics. For the analysis tool used Structural Equation Model which is processed with SmartPLS2 Software. The results of research analysis at RSI Ibnu Sina prove that the location of the hospital, the socioeconomic status of the family, the quality of health services affect patient satisfaction. Family location and patient satisfaction affect patient preferences while the quality of health services does not affect patient preferences. Patient satisfaction has an effect on mediating health service quality variables on patient preferences, but patient satisfaction has no effect on mediating location variables and socio-economic status variables on patient preferences.